Analisis Pengaruh Nilai-Nilai Budaya, Pemberdayaan, Motivasi dan Perilaku Kewargaan terhadap Kinerja Dosen di Universitas XYZ - Zulhawati, . (Universitas Brawijaya, Indonesia, 2015)
This study is aimed in analyzing the effects of cultural values, empowerment, motivation,and citizenship behavior on the lecture's performance. It was conducted with thesubjects of the lecturers of XYZ University in 2012. The data were collected by using a surveymethod involving 142 lecturers as the sample out of the population of 204 lecturers in XYZUniversity. The data of each variable were collected by using different questionnaires andthen were analyzed by using Structural Equation Modeling. The data analysis and interpretationsuggest that the lecture's performance is directly affected by the cultural values, empowerment,motivation, and citizenship behavior. Their citizenship behavior is directly affectedby their cultural values, empowerment, and motivation.The findings lead to the conclusionthat cultural values, empowerment, motivation, and citizenship behavior are determiningfactors for the lecture's performance. They also imply that the performance of thelectures can be improved when their cultural values, empowerment, motivation, and citizenshipbehavior are improved.